NILAI EKONOMI MANFAAT HIDROLOGIS HUTAN DI SUB DAS SOMBE UNTUK KEBUTUHAN KONSUMSI AIR RUMAH TANGGA DI KELURAHAN PALUPI KECAMATAN TATANGA KOTA PALU - Sarah, Sitti; Umar2, Syukur; Alam, Andi Sahri (Universitas Tadulako, 2015)
The hydrological benefit of forest on ecosystem stability,especially on the water system still remains under estimate, this under estimate is more important in the take of using water from the forest for direct community of our people. This study aimed to estimate the quantity economic value or the cost spended by each household in order to have advantage of using water the coming from the Sombe sub watershed which the method of calculating the charge using the rate calculation applicable at PDAM Uwe Lino in M3. This study was conducted at Palupi Sub-district Tatanga District Palu City, Central Sulawesi Which held in 3 month, namely May 2014 up to august 2014. Data collected includes primary and secondary data. Interviews were conducted to obtain data on the economic value water of water that is the willingness to pay on the improvement of the quality and quantity of treated water by PDAM. From water discharge data were obtained data on the economics value of water with the willingness to pay on the improvement of the quality and quantity of treated water by PDAM. From water discharge data or obtained the volume of water use was 0,315 m3/second. Water consumption for a year by the costumer at Palupi Sub-district with the total price paid was Rp.741.248.750m and average total willingness to pay (WTP) by consumer at palupi sub-district was Rp.808.635.000. So, the consumer surplus public at Palupi Sub-district was RP.67.384.250. Keywords: Hidrological benefit, Water discharge, Economic value.